(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we establish the local existence for the generalized Navier-Stokes-Maxwell system with the fractional velocity dissipative term Λ^2αu and fractional magnetic dissipative term Λ^2βB. Moreover, we establish the global existence of strong solutions to this generalized model.